2004
DOI: 10.1002/cbdv.200490107
|View full text |Cite
|
Sign up to set email alerts
|

Efforts towards the Design of ‘Teflon’ Proteins: In vivo Translation with Trifluorinated Leucine and Methionine Analogues

Abstract: In vivo incorporation of monofluorinated noncanonical amino acids into recombinant proteins has been well-established for decades. Proteins fluorinated in this way proved to be useful tools for many practical applications. In contrast, trifluorinated amino acids have been incorporated in only a few peptides and relatively small proteins by using expression systems in living cells. A novel class of proteins with a fluorous core can be envisaged only if full replacement of the core-building hydrophobic and aliph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Recently, Budisa et al (2004) showed the incorporation of trifluorleucine and trifluoromethionine into various proteins over the size of 10 kDa through SPI. Marginal substitution (2-30% by amino acid analysis) was achieved by their method.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Budisa et al (2004) showed the incorporation of trifluorleucine and trifluoromethionine into various proteins over the size of 10 kDa through SPI. Marginal substitution (2-30% by amino acid analysis) was achieved by their method.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] Fluorinated analogues like difluoromethionine (Dfm), trifluoromethio-nine (Tfm) and 6,6,6-trifluoronorleucine (Tfn) have been used as 19 F-NMR probes of protein structure, to increase protein stability and to design teflon-like or "non-stick" proteins. [38][39][40] The more hydrophobic [41] analogues norleucine (Nle) and ethionine (Eth) were used to study overall effects on enzyme activity. Their incorporation in the Met-rich active site of Calmodulin lowered its activity, [42] whereas incorporation of Nle into Lipase from Thermoanaerobacter thermohydrosulfuricus (TTL) led to an enzyme highly active in the aqueous phase without the need for thermal activation [43] and enhanced stability against denaturing agents.…”
Section: Global Reassignment Of the Aug Codonmentioning
confidence: 99%
“…In hindsight, this is not surprising as a CF 3 group should be ~70% bulkier than CH 3 (C-F bond length 1.39 Å vs. C-H 1.09 Å; van der Waals radii of 1.35 Å for F vs. 1.2 Å for H), and may be more hydrophobic as suggested by partitioning studies of hexafluoroleucine and leucine 48 (also see ref. 42 and references therein).…”
Section: Selecting a New Trna Synthetase For A Fluorinated Unnatural mentioning
confidence: 99%